Peran orientasi kewirausahaan dan orientasi pasar untuk meningkatkan kualitas layanan dan kinerja industri hotel - Tricahyadinata, Irsan (Faculty of Economics and Business Mulawarman University, 2016)
This study aims to examine the relationship between entrepreneurial orientation (EO) and market orientation (MO) services quality (SQ), and its impact on organizational performance. Design / methodology / approach: The sampling plan is 273 managers of 273 hotels in East Kalimantan, the study is to bridge the gap and show the importance of entrepreneurial orientation (EO) and market orientation (MO) on service quality (SQ) and organizational performance (OP) in the service organization also provides theoretical contributions to the development of entrepreneurial orientation (EO) and market orientation (MO) in relation to service quality (SQ) and organizational performance (OP). The results showed that 1) EO effect on MO, SQ and PERF, 2) MO not significant effect on PERF and MO significant impact on the SQ, 3) SQ significant effect on PERF. The findings of this study to significantly improve knowledge of the impact of entrepreneurial orientation (EO) and market orientation (MO) on service quality and organizational performance,Keywords: Entrepreneurship Orientation, Service Quality, Market Orientation, Organizational Performance, Hotel Industry